Three new species of the congrid eel genus Gnathophis (Anguilliformes: Congridae) from the Arabian Sea - Kodeeswaran, Paramasivam; Karmovskaya, Emma S. (Zootaxa, 2025)
Three new species of the congrid eel genus Gnathophis viz., Gnathophis ajithi, Gnathophis anilmohapatrai, and Gnathophis arabicus are described herein. Gnathophis ajithi is collected from 264–450 m depth along the Arabian Sea and differs from its congeners in having 2nd, and 7th–8th through 13th–15th pores elevated; small eye, 15.7–17.7% HL; lateral-line pores before anus 27–33, stomach grey to black. Gnathophis anilmohapatrai is collected from 264 m depth and differs from its congeners in that the lateral-line pores above pectoral fin are not elevated, lateral-line pores before anus 36–40, stomach pale. Gnathophis arabicus is collected from 450–600 m depth and differs from its congeners in that the lateral-line pores above pectoral fin are not elevated, lateral-line pores before anus 36–41; SO pores 5, SO5 absent, SO6 present, stomach pale and black posteriorly. Further, CO1 mtDNA sequences are generated and discussed with the sequences available at public domain.